Crystal structure of 6-deoxy-α-l-psicofuranose - Yoshihara, Akihide (Acta Crystallogr E Crystallogr Commun, 2015)
The title compound, C(6)H(12)O(5), was crystallized from an aqueous solution of 6-deoxy-l-psicose (6-deoxy-l-allulose, (3S,4S,5S)-1,3,4,5-tetrahydroxyhexan-2-one), and the molecule was confirmed as α-furanose with a (3) T (4) (or E (4)) conformation, which is a predominant tautomer in solution. This five-membered furanose ring structure is the second example in the field of the 6-deoxy-ketohexose family. The cell volume of the title compound [742.67 (7) Å(3), Z = 4 at room temperature] is only 1.4% smaller than that of β-d-psicopyranose, C(6)H(12)O(6) (753.056 Å(3), Z = 4 at room temperature).